Genotype and allele frequencies of isoniazid-metabolizing enzymes NAT2 and GSTM1 in Latvian tuberculosis patients. Issue 7 (July 2016) - Igumnova, Viktorija; Capligina, Valentina; Krams, Alvils; Cirule, Andra; Elferts, Didzis; Pole, Ilva; Jansone, Inta; Bandere, Dace; Ranka, Renate
Abstract: Pharmacogenomic testing of tuberculosis drug-metabolizing enzyme genes was proposed as a strategy to identify patients at risk for suboptimal responses to medications. However, variations of the genotype frequencies among ethnic groups exist and new alleles are been identified. The aim of this study was to identify polymorphisms of genes encoding metabolic enzymes NAT2 and GSTM1 in tuberculosis patients in Latvia and to estimate the frequency of NAT2 slow acetylator and GSTM1 null genotypes. In total, 85 DNA samples were genotyped, all individuals were Caucasian. An ethnic heterogeneity reflecting the multiethnic population of the country was observed. 49 patients were Latvians, 30 were Russians and 6 of other ethnicity. In total, 7 NAT2 alleles were identified: *4, *5, *6, *7, *11, *12, * and *13. The most frequent was the slow acetylation allele NAT2*6 (frequency 0.388) followed by the slow acetylation allele NAT2*5 and the rapid acetylation allele NAT2*4 (frequencies 0.306 and 0.194, respectively). The predominance of slow (51.8%) and intermediate (43.5%) acetylators compared with rapid acetylators (4.7%) was observed. The GSTM1 null genotype was detected in 48.2% of tuberculosis patients. When subgroup analysis was performed according to ethnicity, the results showed that neither NAT2 allele frequencies nor GSTM1 null genotype frequency did not differ significantly in TB patients of Latvian or Russian ethnicity. Overall, genotyping results were similar with previous reports of a NAT2 gene variation and GSTM1 null genotype frequency in Caucasians. Our findings have a contribution for the pharmacogenetics-based tuberculosis therapy in Latvia in future.